Analisis Faktor Penyebab Rendahnya Bed Occupancy Rate (BOR) di Balai Besar Kesehatan Paru Masyarakat Makassar - Agus Salim; Ervina Rachmawati; Maya Weka Santi; Indah Muflihatin (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2023)
The Bed Occupancy Rate (BOR) at the Makassar Community Lung Health Center in the last 3 years has decreased in 2018 by 64%, in 2019 by 62% and in 2020 by 52%. BOR is an indicator of health services that can be used to determine the level of quality, level of utilization of facilities and efficiency of health services. The impact of the decrease in BOR causes a decrease in economic income for the Hospital. The purpose of this study was to analyze the factors causing the low BOR at the Makassar Community Lung Health Center with (human resources), (facilities and infrastructure), (discipline of health care providers) and (problem improvement efforts. This study used qualitative research methods, with the intention of digging deeper into the factors causing the low BOR by using interview, observation, documentation and brainstorming techniques involving 3 informants including HRD, head of facilities and infrastructure and head of nursing.The results of this study indicate that the factor causing low BOR is the lack of resources. human nurses, facilities and infrastructure are not adequate, the discipline of health service providers is not consistent. The solution is that human resources need to be added to facilities and infrastructure that are immediately improved and complete the facilities and infrastructure that are not yet available.